AB0208 Prevalence of anemia and its relationship with disease activity in patients with rheumatoid arthritis: quest-ra study in morocco. (23rd January 2014) - Hari, A.; Rostom, S.; Lahlou, R.; Benchekroun, B.; Benbrahim, L.; Bahiri, R.; Hajjaj Hassouni, N.
Abstract : Objectives: To evaluate the prevalence of anemia in patients with rheumatoid arthritis and analyze its relationship with parameters of disease activity from the QUEST-RA data Moroccan. Methods: Moroccan QUEST-RA (Quantitative Standard Monitoring Patients with Rheumatoid Arthritis), inspired from Finnish QUEST-RA. Moroccan QUEST-RAis a national multicentric cross-sectional study of patients with rheumatoid arthritis (according to the 1987 ACR criteria) enrolled in public and private sectors, over a period from January 2008 to December 2010. Pre-established questionnaire containing sociodemographic, clinical and paraclinical characteristics was completed by all patients. Patients were divided into two groups: a group with anemia (hemoglobin <13 g / dl in men, <12g/dl in women) and a group without anemia (hemoglobin ≥ 13g/dl in women and ≥ 12g/dl humans) according to the criteria of the World Health Organization. The parameters of disease activity were assessed by EVA patient, EVA doctor, erythrocyte sedimentation rate (ESR), C- Reactive protein (CRP) and DAS-28 ESR. Results: 1129 patients with RA were eligible. The mean age of patients was 48.8 ± 12.7 years with female predominance (87.3%). The median disease duration was 6 years (3-12), the mean DAS28 ESR was 4.94 ± 1.68, the median HAQ was 1 (0.37-1.62). The prevalence of anemia was 28.8%. In univariate analysis, there was a significant association between the presence of anemia, ESR, CRP, HAQ with respectively [(OR = 1.20, 95% CI (1.01-1.40)) (OR = 1.02, 95% CI (1.01 to 1.04)) (OR = 2.07, 95% CI (1.74 to 3.47)) (for all p <0.05)]. Moreover, there was no association between anemia and the presence of comorbidities (ulcer; IDM, vascular pathology ….). In multivariate analysis, only persist an association between anemia, ESR (OR = 1.02, 95% CI (1.01 to 1.06)) and HAQ (OR = 1.04, 95% CI (1.01 to 1.60)) for all p <0.05. Conclusions: This study suggests that the prevalence of anemia was common and appeared to be independently associated with disease activity. Further studies are needed. Acknowledgements: Dr Samir Ahid: Laboratory of Biostatistics, Clinical Research and Epidemiology, Faculty of Medicine and Pharmacy. Rabat. Morocco. Disclosure of Interest: None Declared